The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jcb.26121
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: A Naturally Occurring Modulator of Adipokines in Diabetes

Abstract: Curcumin, the bioactive component of turmeric, has been used for the treatment of several diseases including diabetes and its complications. Curcumin has been shown to exert pleiotropic effects by modulating different signaling molecules, including transcription factors, chemokines, cytokines, and adipokines. Disturbed regulation of adipokines, which include adiponectin, leptin, resistin, and visfatin, are implicated in the development of insulin resistance and Type 2 diabetes. Here, we review the findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 180 publications
1
37
0
Order By: Relevance
“…Curcumin is a yellow pigment extracted from the rhizomes of Curcuma longa L. (turmeric) and has various biological functions, including anti‐obesity and antidiabetic properties . Some experimental animal and clinical trials have indicated that curcumin has a suppressive effect on the accumulation of body fat .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin is a yellow pigment extracted from the rhizomes of Curcuma longa L. (turmeric) and has various biological functions, including anti‐obesity and antidiabetic properties . Some experimental animal and clinical trials have indicated that curcumin has a suppressive effect on the accumulation of body fat .…”
Section: Introductionmentioning
confidence: 99%
“…[10] Curcumin is a yellow pigment extracted from the rhizomes of Curcuma longa L. (turmeric) and has various biological functions, including anti-obesity and antidiabetic properties. [11,12] Some experimental animal and clinical trials have indicated that curcumin has a suppressive effect on the accumulation of body fat. [13][14][15] However, there is little evidence to indicate that curcumin induces the formation of brown-like adipocytes and the molecular mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, curcumin has anti-diabetic effects that could be considered as valuable targets for diabetes mellitus [79].…”
Section: Inflammation and Fibrosismentioning
confidence: 99%
“…Curcumin is the polyphenolic compound that has been traditionally used as a flavoring and coloring agent in most cuisines along with some medical applications to treat various human ailments (Goel, Kunnumakkara, & Aggarwal, 2008). Recently, multiple biological as well as pharmacological activities have been documented for curcumin, including antimicrobial (Jordan & Drew, 1996;Kim, Choi, & Lee, 2003;Mahady, Pendland, Yun, & Lu, 2001;Negi, Jayaprakasha, Jagan Mohan Rao, & Sakariah, 1999;Reddy, Vatsala, Keshamouni, Padmanaban, & Rangarajan, 2005), anti-inflammatory (Ganjali et al, 2014;Mohammadi et al, 2013;Panahi, Alishiri, Parvin, & Sahebkar, 2016;Panahi, Ghanei, Bashiri, Hajihashemi, & Sahebkar, 2015;Panahi, Rahimnia et al, 2014;Panahi, Saadat, Beiraghdar, & Sahebkar, 2014;Panahi, Sahebkar, Parvin, & Saadat, 2012;Sahebkar et al, 2013), antioxidant Esmaily et al, 2015;Panahi, Sahebkar, Amiri et al, 2012;Sahebkar et al, 2013;Sharma, 1976), antidiabetic (Ganjali et al, 2014;Hajavi et al, 2017;Na et al, 2013) and anticancer (Iranshahi et al, 2010;Kuttan, Bhanumathy, Nirmala, & George, 1985;Mahady et al, 2001;Valiahdi, Iranshahi, & Sahebkar, 2013) characteristics. Of note, curcumin is able to treat the toxicity caused by AFB1 (Poapolathep, Imsilp, Machii, Kumagai, & Poapolathep, 2015b).…”
mentioning
confidence: 99%